ANALISIS ISU SOSIO-SAINTIFIK PADA BUKU TEKS BIOLOGI SMA KELAS XII MATERI BIOTEKNOLOGI - Wardani, Friska; Khairuddin, Khairuddin; Rasyidah, Rasyidah (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Socioscientific issues are controversial issues about social problems that have relevance to science. This study aims to determine whether socio-scientific issues in biotechnology lessons Class XII Biology Textbooks used at MAN 2 Medan have met the socio-scientific quality criteria for science learning. There are five quality criteria for socio-scientific issues are authentic, relevant, evaluation, open discussion, and related to science and technology. This research is a type of descriptive research that uses a qualitative approach. Data collection techniques in this study are observation methods and providing socio-scientific issue analysis sheets. The results of this study show that there are three socio-scientific issues in biotechnology lessons in biology textbooks. The three socio-scientific issues are about cell transplantation from pigs to humans, the problem of human clones, and the problem of transgenic plants.  Based on the results of data analysis of the three socio-scientific issues, it shows that the quality of Socio Scientific Issues (SSI) for science learning is obtained at a percentage of 80% or good category, so that these socio-scientific issues are feasible to be applied in biology learning. Kata kunci: Analisis, Buku Teks Biologi, Kualitas Isu Sosio-Saintifik